Telehealth treatment for nonspecific low back pain: A review of the current state in mobile health. Issue 9 (26th January 2022) - Tabacof, Laura; Baker, Turner S.; Durbin, John R.; Desai, Vimi; Zeng, Qi; Sahasrabudhe, Abhishek; Herrera, Joseph E.; Putrino, David
Abstract: Introduction: Nonspecific low back pain (LBP) is an idiopathic musculoskeletal condition that affects four of five individuals in their lifetime and is the leading cause of job‐related disability in the United States. The interest in interactive and dynamic telehealth treatments for LBP continues to grow, and it is important for the medical community to remain up‐to‐date on the state of the science. Literature survey: Relevant studies published from March 2016 until March 2021 were identified through a systematic search of EMBASE, MedLine, and Web of Science. The search strategy combined the concepts of back pain, telehealth, and mobile applications. Methodology: Titles and abstracts were screened to select full‐text randomized controlled trials or protocols, and methodological quality and risk of bias was assessed using the Cochrane risk‐of‐bias tool. Data were synthesized narratively. Synthesis: We included seven concluded randomized‐controlled trials and two study protocols reporting mobile health (mHealth) solutions for LBP. Six of the seven concluded trials found a significant improvement in self‐reported numerical pain rating scale compared to the control group. A single trial compared a mHealth solution to physical therapy, with the majority of studies comparing interventions to "usual care." Substantial heterogeneity in reporting of sample characteristics was found, indicating a lack of standardization through the field. Conclusions: mHealth solutions may positively impact people with LBP. Larger trials should be encouraged and the field should coalesce around a set of baseline variables for collection and reporting. Because many interventions involve patient engagement, future trials should aim to further quantify adherence levels and begin to define telehealth "doses" associated with better outcomes.